Students’ Perceptions of Google Translate Use in English Learning: Vocational High School Context - Ardiyanti Shofia Rahman; Frida Unsiah (JEELS (Journal of English Education and Linguistics Studies), 2025)
This study explores the perceptions of the 10th grade tourism students towards the use of Google Translate in learning English. Using mixed methods, data were collected through questionnaires and semi-structured interviews with 36 students of a vocational high school in East Java, Indonesia. The quantitative data were analyzed using descriptive statistics and the qualitative ones were analyzed thematically. The findings showed that students frequently used Google Translate to translate words, sentences, and paragraphs in academic assignments. The high frequency of the use indicates a fairly high level of reliance, especially among students with lower English proficiency. However, some of the more critical students still checked the translation against other sources to ensure accuracy. While Google Translate facilitates access to English, its limitations in translating tourism terminology may hinder in-depth understanding.      Therefore, it is important that teachers provide supervision and incorporate alternative learning resources to support students in developing more independent and contextualized language skills, such as more accurate digital dictionaries or practice-based methods. With the right approach, Google Translate can be an effective tool without replacing more in-depth learning.